Nanoporous Copper-Nickel – Macroscopic bodies of a strong and deformable nanoporous base metal by dealloying. (October 2018) - Lührs, Lukas; Weissmüller, Jörg
Abstract: Uniform macroscopic samples of nanoporous metal with high deformability have so far been limited to precious metals such as Au, Pd and Pt. Here we propose nanoporous Copper-Nickel (npCN) as a nanoporous base metal that can be made with mm dimensions and exhibits significant deformability. NpCN forms a uniform bicontinous network structure with feature sizes that can be controlled from 13 to 40 nm by thermal annealing. Continuous compression tests confirm ductile deformation behavior accompanied with a high strength compared to macroporous Cu- and Ni-foams with similar solid fraction. Graphical Abstract: